Ridge augmentation using recombinant human fibroblast growth factor‐2 with biodegradable gelatin sponges incorporating β‐tricalcium phosphate: a preclinical study in dogs. (29th May 2015) - Hoshi, S.; Akizuki, T.; Matsuura, T.; Ikawa, T.; Kinoshita, A.; Oda, S.; Tabata, Y.; Matsui, M.; Izumi, Y.
Abstract : Background and Objective: Fibroblast growth factor‐2 (FGF‐2) regulates the proliferation and differentiation of osteogenic cells, resulting in the promotion of bone formation. Biodegradable gelatin sponges incorporating β‐tricalcium phosphate (β‐TCP) have been reported as a scaffold, which has the ability to control growth factor release, offering sufficient mechanical strength and efficient migration of mesenchymal cells. In this study, we evaluated the effects of the combined use of recombinant human FGF‐2 (rhFGF‐2) and gelatin/β‐TCP sponge on ridge augmentation in dogs. Material and Methods: Six male beagle dogs were used in this study. Twelve wk after tooth extraction, bilateral 10 × 5 mm (width × depth) saddle‐type defects were created 3 mm apart from the mesial side of the maxillary canine. At the experimental sites, the defects were filled with gelatin/β‐TCP sponge infiltrated with 0.3% rhFGF‐2, whereas gelatin/β‐TCP sponge infiltrated with saline was applied to the control sites. Eight wk after surgery, qualitative and quantitative analyses were performed. Results: There were no signs of clinical inflammation at 8 wk after surgery. Histometric measurements revealed that new bone height at the experimental sites (2.98 ± 0.65 mm) was significantly greater than that at the control sites (1.56 ± 0.66 mm; p  =   0.004). The total tissue height was greater at the experimental sites (6.62 ± 0.66 mm) than that at the control sites (5.95 ± 0.74 mm), although there was no statistical significant difference ( p  = 0.051). Cast model measurements revealed that the residual defect height at the experimental sites (2.31 ± 0.50 mm) was significantly smaller than that at the control sites (3.51 ± 0.78 mm; p  = 0.012). Conclusion: The combined use of rhFGF‐2 and gelatin/β‐TCP sponge promotes ridge augmentation in canine saddle‐type bone defects.